Analisis Kemitraan PT Astra Agro Lestari Tbk Dalam Pelaksanaan Program Astra Kreatif di Desa Ring 1 Kabupaten Pasangkayu - Askar Mayusa; Muh.Faldi; Keysha Putri Maharani; Afdal Dzikry; Rahmawati Kasman; Nining Vitria; Nur Fadilla; Marcela Angelina Pamora; Muzdalifah Muzdalifah; Audietya Chantieka Aura; Muhamad Riski Nugraha; Aulia Farida; Ratu Amanda; Nanda Aprilia Royna; Nawawi Natsir; Muhammad Afandi (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study analyzes the implementation of PT Pasangkayu's Corporate Social Responsibility (CSR) program in supporting the Creative Indonesia vision. CSR is seen as a corporate strategy to improve community welfare while strengthening social legitimacy through a participatory approach. The Astra Kreatif program implemented by PT Pasangkayu includes fostering oil palm farmer groups, diversifying non-oil palm businesses (cultivating catfish, chilies, laying hens, and mushrooms), and developing MSMEs based on local potential. The results show that this program has succeeded in improving farmers' technical and managerial skills, opening alternative business opportunities, strengthening the role of women and youth in the village economy, and creating solid social networks. The tangible impact is seen in 475 heads of families in four main target villages, who receive direct economic benefits and increased independence. Thus, PT Pasangkayu's CSR through Astra Kreatif contributes to inclusive and sustainable village economic development and enriches the discourse of Creative Indonesia from local roots to the national level.